Relationship between morphology and severity of septal deformity and the degree of nasal obstruction - Hoang, Phuoc Minh; Phan, Thi Khanh Trinh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Objectives: The correlation between the type and severity of septal deviation and the degree of nasal obstruction remains unclear. This study aimed to evaluate this relationship using three patient-reported measures of nasal obstruction in conjunction with peak nasal inspiratory flow (PNIF). Methods: A total of 212 subjects from a general ENT clinic were included. Patients reported symptoms using the NOSE scale and a visual analog scale (VAS). PNIF was measured, and septal deviation was classified according to the Mladina classification (type) and the Salihoglu classification (severity). Results: The mean NOSE, VAS, and PNIF values were 28.6, 5.3, and 96.8 L/min, respectively. Only the NOSE score showed a significant correlation with septal deviation type, severity, and PNIF. Septum with bilateral vertical deformities had the highest NOSE scores and the lowest PNIF values. Conclusions: Subjective symptom scores demonstrated limited correlation with PNIF. Decisions regarding septoplasty should integrate patient history, physical examination, and both subjective and objective assessments.